Pengaruh Integrasi Latihan Gerak Dasar Pendidikan Jasmani terhadap Perkembangan Motorik Siswa SD diMasa Pandemi Covid-19 - Alek Oktadinata; Herman Subarjah; Komarudin; Yusuf Hidayat; Ilham (Elementary Teacher Education Program, Majalengka University, 2023)
Basic movement proficiency (FMS) is most successfully acquired during the early school years. This happens at the beginning and after 2.5 years of primary school physical education. The purpose of this study was to examine the effect of selected exercises on motor development in first year elementary school students in Jambi City, Indonesia. This research is semi-experimental in nature, carried out in the field and using experimental and control groups. The statistical population includes all first-year elementary school students in Jambi city (7523 students). Fifty-six of them were randomly selected (cluster stage) and then randomly divided into two groups: experiment (N=26, mean age=6.9 ± 0.55) and control (N=28, mean age). average = average = 6.9 ± 0.59). ). The experimental group was given training for eight weeks, 2 sessions per week and each session lasted 45 minutes. To measure motor development, the Test of Gross Motor Development edition 2 (TGMD-2) is used. Statistical analysis was performed using independent t-test and paired t-test. The results showed a statistically significant difference between the control and experimental groups regarding movement skills (8.637, P<0.05). In fact, the integration of basic motion exercises in physical education has an impact on their motor development. By integrating basic movement exercises, it can be used as an appropriate plan to improve the development of movement skills in first-year elementary school students.